The Unicorn's Shadow Combating the Dangerous Myths that Hold Back Startups, Founders, and Investors - Mollick, Ethan (University of Pennsylvania Press, 2020)
Bringing hard data to the way we think about entrepreneurial success, this bold call to action draws on the latest scientific evidence to dispel the most pervasive startup myths and light a path to entrepreneurship for those eclipsed by the hype.When you think of a successful entrepreneur, who comes to mind? Bill Gates? Mark Zuckerberg? Or maybe even Jesse Eisenberg, the man who played Zuckerberg in The Social Network? It may surprise you that most successful founders look very different from Zuckerberg or Gates. In fact, most startup origin stories are very different from the famous "unicorns" that have achieved valuations of over $1 billion, from Facebook to Google to Uber.In The Unicorn's Shadow: Combating the Dangerous Myths that Hold Back Startups, Founders, and Investors, Wharton School professor Ethan Mollick takes us to the forefront of an empirical revolution in entrepreneurship. New data and better research methods have overturned the conventional wisdom behind what a successful founder looks like, how they succeed, and how the startup ecosystem works.Among the issues he examines:Which founders are most likely to succeed?Where do the best startup ideas come from?What's the most foolproof way of securing the funding needed to take a company to the next level?Should your sales pitch really be something out of Hollywood?What's the best way to grow and scale your company and create a thriving culture that won't hinder expansion?Mollick argues that entrepreneurship is too important, both for society and for the individuals who start companies, to be eclipsed by the shadows of unicorns. He shows we can democratize entrepreneurship-but only by following an evidence-based approach that puts to rest the false narratives that surround it